Pengaruh Tagline dan Brand Ambassador terhadap Representasi Makna Iklan Sasa: Kajian Semiotik - Fitria Lonanda; Ummi Rasyidah; Roswati Roswati; Yessi Ratna Sari; Qori Islami Aris; Essy Syam (Lingua Susastra, 2022)
Advertising is a form of promotion of a product, goods or service by a company to the public. Closely related to promotional events, especially the target market of food lovers, the seasoning company Sasa not only advertises its products but also creates magic through the tagline it uses. The data is in the form of a 1 minute 30 second Sasa ad video downloaded on Sasa's YouTube channel. This advertisement stars Choi Siwon, a famous South Korean singer. Siwon is described as a chef who gives miracles and happiness to everyone through Sasa's seasoning. The analysis was carried out using a descriptive qualitative method with a semiotic approach by Charles Sanders Peirce, namely looking at the signs and meanings that are present as a representation. This study aims to find the meaning contained in the Sasa video advertisement with the tagline "Untuk Hidup Penuh Keajaiban". The data used in the form of verbal and visual that refers to the tagline and the image. The results of the research show that the magic that is given by the Sasa product is to spread happiness throughout the country through the concoction of the Sasa cooking seasoning variant. The tagline and icon used have an influence on the image of a product. From the tagline it is illustrated that the miracle of life can be obtained through Sasa. Likewise with the Sasa and Siwon logos as icons that have become worldwide, namely spreading magic to all connoisseurs of Sasa seasoning.